The impact of the development of information technology in accelerating Sharia audits (Jordan Islamic Bank as a model) - Al-Saad, Ahmad; Al-Hamdan, Fatima (Jordan Journal of Islamic Studies, 2023)
The study aimed to know the employment of information technology in sharia audit, the study addressed the definition of information technology, its importance and history in sharia audit, and the study enumerated the methods of auditing in information technology, and then the study presented the model of using the information technology in sharia audit on the Jordan Islamic Bank, and the study reached that there is a cooperative relationship between the management of information systems and sharia audit, and that the human component still has a major role in the sharia audit process, and the researcher saw the need to design a program and sharia audit that reduces the intervention of the human component to reduce errors that occur.